Dimensi Psikososial Persaraan (Psychosocial Dimension of Retirement) - Adi Fahrudin; Husmiati Yusuf; Mohd Dahlan HA Malek; Wan Anor Wan Sulaiman (2016)
Retirement is a unique phenomenon experienced by an individual who works very formal. One marker of retirement is lost in many aspects, including income, activities, identit themselves and friends as a source of support. For individuals who do not have the preparation, retirement is a burden that can give psychosocial implications not only to him but also to the family and society. Therefore it is necessary that there is a program that can help workers prepare yourself both before and after retiremen